Family caregiving for older adults: gendered roles and caregiver burden in emigrant households of Kerala, India - Allen Prabhaker Ugargol & Ajay Bailey (Asian Population Studies, 2018)
The Indian state of Kerala leads the demographic transition and characteristically showcases emigration of predominantly male adult children, leaving behind parents, spouses and children. When men emigrate, gendered contexts burden women, especially spouses and daughters-in-law, with caregiving duties including elder care. Employing the social exchange Perspective and drawing on in-depth interviews of left-behind caregivers to older adults in emigrant households, we explore reciprocal motives, exectations and perceptions of burden. Findings resonate gendered expectations of care and social sanction that ensure women do much of the caregiving. Daughters-in-law sacrificed careers and endured separation from husbands to transition into caregiving roles, costs borne to effectuate their husband’s filial role. Perceived non-reciprocity, unbalanced exchanges and unmet expectations increased perceptions of burden for caregivers. Temporary financial autonomy could hardly alleviate perceptions of burden among women caregivers who perceived emotional and functional support exchanges from husbands, older adults themselves or other family members as supportive.